China’s Ambiguous Impacts on Commodity-Dependent Countries: the Example of Sub-Saharan Africa (with a Focus on Zambia) - (:unkn) unknown (My University, 2012)
The spectacular growth of China has induced major changes for developing countries, in particular low-income Sub-Saharan African economies. Most of these economies heavily depend on primary commodities for their exports, and China’s demand for these commodities, especially oil and metals, has contributed to a long cycle of increase in commodity prices (the ‘supercycle’ of the 2000s), but also to increased price volatility. China has also become a significant trade partner of Sub-Saharan African economies, and invested significantly in Sub-Saharan Africa. A theoretical question is therefore whether these changes may generate structural transformation and trigger sustained growth paths in Sub-Saharan countries. The paper shows that the transmission channels of China’s impact on growth prospects in Sub-Saharan African economies are multiple, both direct and indirect, and underscores the ambivalence of these impacts: i) high commodity prices have the potential to improve fiscal space, creating opportunities to catalyse diversification and structural transformation. Moreover, Chinese investments occur not only in the commodity sectors but also in industrial sectors and infrastructure; ii) however, higher and more volatile commodity prices, driven by China, can result in negative effects (e.g., Dutch disease). Furthermore, China’s demand may lock African economies into their century-old pattern of dependence on primary commodities. Large Chinese investments (especially in infrastructures) may also have lock-in effects, as they are organised by original contracts that exchange investments for commodities; iii) it is particular commodity and industry factors that affect an individual country’s ability to harness opportunities created by high commodity prices, which is demonstrated via the case study of Zambia.
Keywords: African Research